Comparison of Acute-Phase Pain Intensity, Pain Trajectory, and the Number of Analgesics Administered between Total and Unicompartmental Knee Arthroplasties - Oka, Tomohiro; Imai, Ryota; Wada, Osamu; Mizuno, Kiyonori (The Journal of Knee Surgery, 2022)
We aimed to compare the variables of pain intensity, pain trajectory, and the number of analgesics administered during the acute phase between total and unicompartmental knee arthroplasties. This prospective cohort study recruited 445 patients who planned to undergo knee arthroplasty. Pain intensity was evaluated during hospitalization, and 1 month postoperatively using a numerical rating scale. Pain trajectory (slope and intercept) was calculated using pain intensity data from postoperative days 1 to 4. The number of analgesics administered for worsening pain was monitored during hospitalization. Multiple linear regression analysis with adjustment for potential confounders was conducted to investigate the impact of surgery type on pain variables. Data for 208 and 189 patients who had undergone total and unicompartmental knee arthroplasties, respectively, were included in this study. Pain intensity and pain trajectory were similar between the two surgeries. The number of analgesics administered on postoperative day 3 (p = 0.01) and day 4 (p = 0.03), as well as total number (p = 0.01), were lower for unicompartmental knee arthroplasty than for total knee arthroplasty. Multiple linear regression analysis showed that the type of surgery affected the total number of analgesics administered (β = − 1.24, p < 0.01, 95% confidence interval: −1.80 to −0.62). This study suggests that pain characteristics observed during the acute phase differ between total and unicompartmental knee arthroplasties. Postoperative pain should be managed, and rehabilitation should be provided at similar levels after the second postoperative day in total and unicompartmental knee arthroplasty patients.
Keywords: total knee arthroplasty; unicompartmental knee arthroplasty; acute postoperative pain; number of analgesics administered